Report of Irrigation and Power Team on Rihand Project (Uttar Pradesh) - Planning Commission (Planning Commission, 1962)
The Committee on Plan Projects, which was set up by the National Development Council in 1956. appoints, from time to time. Teams to make studies of different categories of projects included in the Five Year Plans with a view to securing economy and efficiency in their implementation. One such Team was appointed for the study of Rihand Project vide Committee on Plan Projects letter No. COPP/(4)/8/59 dated August 24, 1959.
Committee on Plan Projects
Committee on Plan Projects